1998
DOI: 10.1007/bf02237481
|View full text |Cite
|
Sign up to set email alerts
|

DNA index as a significant predictor of recurrence in colorectal cancer

Abstract: The DNA index value (less than or greater than 1.4) seems to be a stronger predictor than DNA ploidy (diploid or aneuploid), and the combination of Dukes stage, tumor site, and a DNA index is, therefore, considered to be clinically valuable in predicting recurrence in cases of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…In these 25 studies, it was observed that the duration of followup was inaccurate or did not reach five years after surgical treatment. Nineteen studies 29,48,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] were excluded because of impossible data extraction. In these studies, survival data tables or curves at fiveyear follow-up were not available or absolute death numbers were available but the group size was not determined at the beginning of follow-up or after five years.…”
Section: Discussionmentioning
confidence: 99%
“…In these 25 studies, it was observed that the duration of followup was inaccurate or did not reach five years after surgical treatment. Nineteen studies 29,48,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] were excluded because of impossible data extraction. In these studies, survival data tables or curves at fiveyear follow-up were not available or absolute death numbers were available but the group size was not determined at the beginning of follow-up or after five years.…”
Section: Discussionmentioning
confidence: 99%
“…À luz do grande avanço no campo dos métodos de imagem, genética e marcadores biomoleculares [30][31][32][33] , os achados anatomopatológicos ainda são, na maioria das vezes, os mais importantes, acessíveis e fundamentais fatores na determinação da sobrevida e decisão sobre a aplicação de terapia adjuvante. Há porém, grande controvérsia na literatura médi-ca quanto a relação de significância de alguns deles com a sobrevida dos pacientes portadores de câncer colorretal.…”
Section: Discussionunclassified
“…Altogether 8 of 21 studies (38.1 %) stated statistical significance for survival differences with regard to the ploidy status for the entire collective of Dukes stage A to D CRC [35,39,72,40,44,73,38,45]. Out of these, evaluating the individual tumor stages, not more than two stages per study showed significances in survival.…”
Section: Survival Differences In Individual Tumor Stagesmentioning
confidence: 91%
“…Twelve of 20 (60 %) studies reported a significant difference in survival with aneuploid tumors implying a worse prognosis in either OS, DSS, or RFS [14,15,32,33,70,63,67,71,38,39,72,40]. There were 12 studies which performed a multivariate analysis for OS.…”
Section: Flow Cytometrymentioning
confidence: 94%
See 1 more Smart Citation